Globale Ophthalmologie: aktueller Stand: CME : zertifizierte Fortbildung - Philippin, Heiko; Morny, Enyam K. A.; Heinrich, Sven P.; Töws, Ingrid; Maier, Philip C.; Guthoff, Rudolf F.; Qureshi, Babar M.; Reinhard, Thomas; Burton, Matthew J.; Finger, Robert P. (Die Ophthalmologie, 2024)
The aim of global ophthalmology is to maximize vision, ocular health and functional ability, thereby contributing to overall health and well-being, social inclusion and quality of life of every individual worldwide. Currently, an estimated 1.1 billion people live with visual impairment, 90% of which can be prevented or cured through largely cost-effective interventions. At the same time, 90% of people affected live in regions with insufficient eye health coverage. This challenge drove the World Health Organization (WHO) and a group of nongovernmental organizations to launch “VISION 2020: the Right to Sight”, a global campaign which recently concluded after 20 years. The achievements, challenges and lessons learned were identified and incorporated into the current campaign “2030 IN SIGHT”.